Software for Generating Reports of Automated Tests Using RPA in Web Applications - Arévalo, Fernando R. (2023)
Many companies have adopted the Agile methodology for software project implementation, which involves an iterative and incremental approach. This introduces changes to the software testing lifecycle, as the developed functionalities need to be validated in each iteration. Thus, to avoid manual testing and human error, test automation emerges as a technique for executing functional tests. However, automating tests and analyzing their results in Agile environments can be a complex process due to constantly changing requirements. Therefore, this study focuses on the development of software for generating reports of automated tests, presenting key performance indicators that measure the efficiency and effectiveness of the testing process. Additionally, RPA technology was used for the automation and execution of functional tests in web applications. Finally, the satisfaction level of the developed software was validated with a group of users, resulting in a 46.72% improvement in user perception regarding the ease of performing tasks with the proposed solution compared to the current context in their workplaces. © 2023 CISCI 2023 - Vigesima Segunda Conferencia Iberoamericana en Sistemas, Cibernetica e Informatica, Vigesimo Simposium Iberoamericano en Educacion, Cibernetica e Informatica, SIECI 2023